CHILDREN’S PRAGMATIC COMPETENCE (ISSUE ON FIRST LANGUAGE ACQUISITION) - Diah Ekawati (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2014)
Having a competence of a language means knowing how to use the language properly, both in terms of the grammatical and lexical aspects and in terms of the other social aspects that underlying the use of the language. Pragmatic competence includes in the social aspects that must be owned by speakers of a language. Pragmatic competence involves illocutionary competence and sociolinguistic competence.Children acquire this competence through people surounding them. They acquire it in some stages. Firstly, they learn hor to understand and make inference in daily conversation. Then they learn how to perform an act via utterances. The last is they learn how to say something politely. This competence becomes improved as children get older.